Diagnosis of Diabetes Measurements with A Glucometer (Eurasian Medical Research Periodical, 2022)
Diabetes mellitus, causes of diabetes mellitus, main causes of the development of the disease, symptoms, diagnosis, determination of blood glucose levels, treatment of diabetes mellitus, insulin therapy.